GREEN FINTECH: THE ROLE OF TECHNOLOGY IN PROMOTING SUSTAINABILITY IN FINANCIAL MARKETS - Makhrus Ali; Amin Zaki; Zain Nizam (Yayasan Adra Karima Hubbi, 2026)
The rapid expansion of financial technology has reshaped financial markets, creating new opportunities to address sustainability challenges through innovative digital solutions. Green fintech has emerged as a critical intersection between technology, finance, and sustainability, enabling more efficient allocation of capital toward environmentally and socially responsible activities. This study aims to examine the role of green fintech in promoting sustainability within financial markets and to assess how technological innovations contribute to environmental, social, and governance objectives. The research employs a qualitative–quantitative mixed approach, combining a systematic review of recent academic literature with secondary data analysis of green fintech applications, including digital payments, sustainable investment platforms, and climate-risk analytics. The findings indicate that green fintech enhances market transparency, improves access to sustainable finance, and supports better risk assessment related to environmental impacts. Technological tools such as big data analytics, artificial intelligence, and blockchain are shown to strengthen sustainability integration by reducing information asymmetry and transaction costs. The study also reveals that regulatory support and institutional readiness significantly influence the effectiveness of green fintech initiatives. In conclusion, green fintech plays a strategic role in accelerating the transition toward sustainable financial markets by aligning technological innovation with sustainability goals. However, coordinated regulatory frameworks and cross-sector collaboration are essential to maximize its long-term impact and scalability.